3D graphene/fly ash waste material for hybrid supercapacitor electrode: specific capacitance analysis 3D-Graphen/Flugasche Abfallmaterial für Hybrid-Superkondensatorelektrode: Spezifische Kapazitätsanalyse - Pransisco, P. (Wiley-VCH Verlag, 2020)
The performance of supercapacitor energy storage is depending on the type of the material that is used as supercapacitor electrode. Graphene has been widely used as the base material for a lot of applications due to its remarkable properties. In this research, we try to combine 3D Graphene with waste material fly ash to be used as the electrode of supercapacitor. Fly ash is a residual material from burning pulverized coal in electric generation power plants which contain metal oxide materials such as iron oxide and aluminum oxide. This residual material might be usable as an electrode for supercapacitor due to its material contained. As the base material, the 3D graphene was successfully fabricated by using low pressure chemical vapor deposition (LPCVD) method and afterwards the fly ash was coated on the top of 3D graphene. The chemical properties and surface structure of the electrode material was studied by using Raman spectroscopy and field emission scanning electron spectroscopy (FESEM). 3 electrode systems were used to analyze the cyclic voltammetry results. According to the results, they show that the highest specific capacitance of 3D graphene/fly ash (FA) was about 0.025 F/cm2 at the lowest scan rate of 5 mV/s and it is recommended to use as the supercapacitor electrode. © 2020 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim